2004
DOI: 10.1152/ajpendo.00582.2003
|View full text |Cite
|
Sign up to set email alerts
|

Plasma ghrelin levels and hunger scores in humans initiating meals voluntarily without time- and food-related cues

Abstract: .-Ghrelin is an orexigenic hormone that is implicated in meal initiation, in part because circulating levels rise before meals. Because previous human studies have examined subjects fed on known schedules, the observed preprandial ghrelin increases could have been a secondary consequence of meal anticipation. A causal role for ghrelin in meal initiation would be better supported if preprandial increases occurred before spontaneously initiated meals not prompted by external cues. We measured plasma ghrelin leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
273
2
17

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 444 publications
(312 citation statements)
references
References 57 publications
20
273
2
17
Order By: Relevance
“…Ghrelin levels increase pre-prandially (Cummings et al 2001) and have been shown to correlate with hunger scores in healthy subjects (Cummings et al 2004) indicating that, at least in normal physiology, acute changes of ghrelin may have a role in the decision to eat and/or serve as a circulating hunger hormone. Studies in rodents exploring the precise parenchymal targets for ghrelin's orexigenic effects have identified a number of candidate sites: orexigenic responses have been observed when injected into discrete brain areas that include the hypothalamus (arcuate nucleus, ventromedial nucleus, dorsomedial nucleus, paraventricular nucleus, lateral hypothalamus) (Olszewski et al 2003a;Olszewski et al 2003b;, the nucleus tractus solitarius of the brainstem (Faulconbridge et al 2003), the central nucleus of the amygdala (Olszewski et al 2003) and mesolimbic reward areas (the ventral tegmental area (VTA) and nucleus accumbens (N.Acc) Naleid et al 2005).…”
Section: The Central Ghrelin Signalling Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Ghrelin levels increase pre-prandially (Cummings et al 2001) and have been shown to correlate with hunger scores in healthy subjects (Cummings et al 2004) indicating that, at least in normal physiology, acute changes of ghrelin may have a role in the decision to eat and/or serve as a circulating hunger hormone. Studies in rodents exploring the precise parenchymal targets for ghrelin's orexigenic effects have identified a number of candidate sites: orexigenic responses have been observed when injected into discrete brain areas that include the hypothalamus (arcuate nucleus, ventromedial nucleus, dorsomedial nucleus, paraventricular nucleus, lateral hypothalamus) (Olszewski et al 2003a;Olszewski et al 2003b;, the nucleus tractus solitarius of the brainstem (Faulconbridge et al 2003), the central nucleus of the amygdala (Olszewski et al 2003) and mesolimbic reward areas (the ventral tegmental area (VTA) and nucleus accumbens (N.Acc) Naleid et al 2005).…”
Section: The Central Ghrelin Signalling Systemmentioning
confidence: 99%
“…For a review on this topic, we refer the reader to Skibicka and Dickson 2011. In normal weight healthy volunteers, ghrelin has been shown to increase hunger scores, to enhance food palatability and to increase caloric intake in a free-feeding buffet situation (Cummings et al 2004;Druce et al 2006;. One recent study of food economics reported that ghrelin even increases the amount of money an individual is prepared to pay for individual food items (Tang et al 2011).…”
Section: The Central Ghrelin Signalling System Is Required For Rewardmentioning
confidence: 99%
“…Only Louis-Sylvestre (Himaya et al, 1997) used the meal demand paradigm to measure the impact of preloads on satiety. Those data were later linked to the participants' ghrelin levels, providing a valuable link between data from the behavioral preload paradigm and plasma levels of hunger and satiety hormones (Cummings et al, 2004).…”
Section: Experimental Designsmentioning
confidence: 99%
“…Due to lack of normative data on obestatin in humans when the study was performed, subject numbers were based on recruitment and the minimum numbers needed in previous published work on ghrelin profiles in humans. 18 Obesity was defined as BMI430 kg/m 2 according to the criteria of the World Health Organisation and the International Obesity Task Force. All gastrectomy subjects underwent total gastrectomy for gastric carcinoma at least 12 months previously and were in remission (all had no evidence of recurrence by gastroscopy within the last 12 months).…”
Section: Subjectsmentioning
confidence: 99%